2022
DOI: 10.3390/nu14040859
|View full text |Cite
|
Sign up to set email alerts
|

Are We Sentenced to Pharmacotherapy? Promising Role of Lycopene and Vitamin A in Benign Urologic Conditions

Abstract: Benign prostatic hyperplasia, urolithiasis, recurrent urinary tract infections, and chronic prostatitis are diseases that are commonly diagnosed worldwide. Carotenoids, including lycopene, are widely available in fruits and vegetables, and it is postulated that they can be used in the prevention and treatment of benign urological conditions. The aim of this review is to familiarize doctors and their patients with the current knowledge on carotenoids and their conversion products in selected urological diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Cicero et al in 2019, and Kutwin et al in 2022 published comprehensive reviews on lycopene as a dietary supplement for the treatment of LUTS/BPH [ 119 , 163 ]. In brief, oral lycopene at doses ranging from 10 mg to 500 mg, usually taken twice per day from 2 weeks to up to 6 months, in general, significantly improved LUTS/BPH symptoms (covering over 1000 subjects within an age range of 45–80 years) without adverse effects.…”
Section: Nutraceutical Therapies For Bphmentioning
confidence: 99%
See 1 more Smart Citation
“…Cicero et al in 2019, and Kutwin et al in 2022 published comprehensive reviews on lycopene as a dietary supplement for the treatment of LUTS/BPH [ 119 , 163 ]. In brief, oral lycopene at doses ranging from 10 mg to 500 mg, usually taken twice per day from 2 weeks to up to 6 months, in general, significantly improved LUTS/BPH symptoms (covering over 1000 subjects within an age range of 45–80 years) without adverse effects.…”
Section: Nutraceutical Therapies For Bphmentioning
confidence: 99%
“…In brief, oral lycopene at doses ranging from 10 mg to 500 mg, usually taken twice per day from 2 weeks to up to 6 months, in general, significantly improved LUTS/BPH symptoms (covering over 1000 subjects within an age range of 45–80 years) without adverse effects. The patients were classified as having moderate or severe LUTS/BPH symptoms according to IPSS values before lycopene treatment was initiated [ 119 , 163 ]. Furthermore, other comprehensive reviews on the health benefits of lycopene have been reported elsewhere [ 159 , 160 , 161 ].…”
Section: Nutraceutical Therapies For Bphmentioning
confidence: 99%